Invasão biológica por espécies arbóreas exóticas no Parque Estadual Lago Azul, Paraná : aspectos ecológicos das comunidades vegetais e diretrizes para o manejo. - Zampar, Rafael (2014)
The presence of invasive alien species in protected areas is of concern and studies that prove its impacts to management actions are to be applied. This study was developed to evaluate the impacts caused by the presence of Syzygium cumini and Adenanthera pavonina on the structure and diversity of the tree component of the vegetation of the Lago Azul State Park, Paraná, and provide subsidies for management. We tested the hypothesis that formation of dense canopy cover of S. cumini is a negative effect on regeneration of vegetation in secondary forests. Through a phytosociological study it was found that the presence of exotic species in prominent positions in the amount of importance is altering the structural aspects of vegetation. Furthermore, negative relationships between canopy cover and density of plants and species diversity in the upper and middle strata of vegetation were observed. Was also found negative influence on regeneration of vegetation below the canopy had lower affluence, diversity and density compared to an area without the influence of the species. These impacts should be caused by the formation of dense canopy that prevents the entry of sunlight, or the ability of the plant to release allelopathic compounds in the soil. About A. pavonina the hypotheses tested were that the species diversity in areas occupied by A. pavonina is lower than in non-occupied areas and the species that are presenting invasive potential in the area due to its dispersal potential. These hypotheses were confirmed as the species showed high importance values in the phytosociological survey in the invaded area, which resulted in significant differences in the diversity compared to other areas of the area and that the species has dispersed more than 100 m away from the source of dispersion. Therefore even if not present in recent checklists of invasive alien species, A. pavonina is a species should be considered invasive for Brazilian flora and thus actions to control and possible eradication are required. Because of this we tested experimentally physical and chemical control methods of A. pavonina in Lago Azul State Park, Paraná, and the responses of control over the regeneration of woody vegetation. In a field experiment adults were ringed and young were cut with and without application of the herbicide Triclopyr, and with maintenance and removal of biomass from the cuts. Only treatments of the herbicide were effective in controlling exotic. There was an increase of diversity after the experiment which shows that removal of exotic can contribute to the recovery environment. The recovery of the regeneration vegetation occurred similarly between all the treatments indicating that removal of biomass from the local management is not required. Continued monitoring is necessary because despite the increased diversity, the exotic is still present in regeneration.